1995
DOI: 10.1597/1545-1569(1995)032<0025:tocpaw>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cleft Palate Associated with Robin Sequence: Appraisal of Risk Factors

Abstract: Mandibular hypoplasia, airway obstruction, and a typical wide U-shaped cleft palate comprise the Robin sequence. Although much has been written regarding the treatment of these patients in the neonatal period, the literature reveals little information regarding later care of the cleft palate in these patients. The purpose of this study is to examine patients with the Robin sequence and evaluate the risk of postsurgical problems and outcome related to the neonatal period. Thirty-six patients with the Robin sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…On the other hand, craniofacial morphology within the PRS group in this study did not vary signScantly with regard to cleft extent. Associated anomalies were also commoner in the PRS group (20°/0) than in the ICP group (12%) but were not deviant, as reported in other studies (24)(25)(26). The difference in the: distribution of operation methods between the Veau--Warddl-Kilner (VK) and Cronin (C) modlfication in the PRS and ICP group may also have had some effect on the results.…”
Section: Downloaded By [University Of Otago] At 17:22 11 July 2015supporting
confidence: 68%
“…On the other hand, craniofacial morphology within the PRS group in this study did not vary signScantly with regard to cleft extent. Associated anomalies were also commoner in the PRS group (20°/0) than in the ICP group (12%) but were not deviant, as reported in other studies (24)(25)(26). The difference in the: distribution of operation methods between the Veau--Warddl-Kilner (VK) and Cronin (C) modlfication in the PRS and ICP group may also have had some effect on the results.…”
Section: Downloaded By [University Of Otago] At 17:22 11 July 2015supporting
confidence: 68%
“…Three studies 9,13,14 examined hyponasality of both groups; all found no difference between groups. Three studies 9,11,12 examined the nasal emission of both groups; one study 9 showed increased nasal emission in PRS group. The results of study 5 13 were the final results after velopharyngeal insufficiency (VPI) treatment, which was different from other studies.…”
Section: Resonancementioning
confidence: 99%
“…Patients with Pierre Robin sequence and other identified syndromes have been reported to have an increased risk of developing airway obstruction, respiratory distress, severe feeding difficulties, and even death after palatoplasty (2,3,5). Airway morbidity after Wardill-Kilner or von Langenbeck and recently Furlow repair, but not Perko-revised palatoplasty, has been described (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%